Modern Russian Universities: Positioning, Development Trends, Potential to Enhance Competitive Advantages - M. V. Seroshtan; N. P. Ketova (Moscow Polytechnic University, 2020)
The article focuses on the main trends in the development of modern Russian education. The authors reveal some of its sore points, show the possibilities to overcome them. Some positive examples of the leading universities of the country confirm the high importance of modern University centers of learning, science and culture in the formation of a competence-oriented national educational cluster of innovative type. The authors come to a conclusion that Russian universities, taking into account the existing motivation and the targeted state support provided for them, are able to become quite competitive, to join the ranks of the world top universities, to be attractive not only for Russian but also foreign students. The authors make the case for the the competitiveness growth of the leading universities, argue that the increase of their competitive advantages can become one of the drivers of the development of Russian higher education and the country's economy as a whole.